Implementation of Public Servant Recruitment Towards Disabilities in Jakarta and East Java - Sakinah, Nada (UI Scholars Hub, 2013)
The Constitution of Republic of Indonesia guarantees every citizen – without exception – to have the equal right to get a proper occupation and a decent living, for humanity, this means citizens with disabilities have the same right along with others; this research describes the implementation of policies related to recruitment of civil servants, especially where disabled people are involved as applicants. By applying qualitative method, data collection of this research is done through an in-depth interview and supporting data on recruitment process from related institutions. This research had captured problems within recruitment process for disabled people in every aspect of recruitment such as human resources (HR) planning, job analysis, HR formation, HR procurement and portrayed problems that government agencies face to implement the non-discrimination and affirmative action principles to disabled people in their recruitment processes.